PERKEMBANGAN IMPLEMENTASI DAN TEKNOLOGI PENGENDALIAN HAMA TERPADU PADA TANAMAN KAKAO DI INDONESIA - Araz Meilin (Universitas Batanghari Jambi, 2011)
Indonesia's cocoa plantations have a commodity is the value of exports. It has beenin, there are many constraints in increasing productivity. One is a pest and disease attacks. Government programs through Integrated pest control (PHT) on commodities cocoa plantation has pioneered since 1997 on five commodities including cocoa crops in some areas of Indonesia and in 2002 developed into six commodity in 12 provinces. The implementation of IPM through technology and Airy School IPM Integrated Pest Control (SL-PHT). The technology of PHT to control Fruit Penggerek Cocoapangkasan forms, such as harvesting, biological control, insecticide applications andveiling of the fruit; to control ladybirds MacGregor of the fruit are mechanically, technically cultures, biological and chemical; While the rotten fruit disease to control cocoa is sanitation, reducing moisture, cocoa crop planting and use of fungicide resistant. In addition to technology, SL-PHT was also very instrumental in the implementation of IPM in the cultivation of cocoa. Implementation of SL-PHT much improve the knowledge and skills of cocoa farmers in the cultivation of cocoa and have a positive impact in the implementation of IPM in plantations of cocoa. In line with this, then the implementation of IPM in the cocoa plantations of the people can be made sustainable if there is synergy between farmers, Governments, NGOs and related markets.Keywords: Cocoa, PHT, SL-PHT, PHT Cocoa Technology